Error treatment strategies: preferences of low proficiency English learners - Abu Bakar, Siti Zarikh Sofiah; Mohd Yusof, Fairuz Husna; Sulaiman, Normala (2015)
This study aims to identify students' preferences regarding instantaneous versus delayed error correction and to investigate whether students prefer correction from lecturers or peers. As stated by Xie and Jiang (2007), few teachers possess extensive knowledge of error analysis and related theories. Hendrickson (1978) identified that some teachers are unaware of their error correction methods or how to avoid employing strategies that might embarrass or frustrate students. Furthermore, previous research also indicated that some students felt demotivated and frustrated when their errors were corrected instantaneously by their lecturers. Therefore, this study aims to address concerns regarding the employment of appropriate error treatment strategies for students. Consequently, a sample of ten Pre-Diploma students, enrolled in English for Pre-Diploma (ELC030) at Universiti Teknologi Mara Cawangan Johor, was involved in this study. Purposive sampling was used to select the participants. Data were collected through interviews conducted after the students had received error treatment. The obtained data were analyzed using content analysis. Consistent with previous research, students preferred to be corrected at a later time rather than instantaneously. They were also more comfortable being corrected by their peers compared with their lecturers.